Answer:
x = 1, x = 2
Explanation:
Given
3x(x - 2) = x² - 4 ← distribute parenthesis on left side
3x² - 6x = x² - 4 ( subtract x² - 4 from both sides )
2x² - 6x + 4 = 0 ( divide through by 2
x² - 3x + 2 = 0 ← in standard form
Consider the factors of the constant term (+ 2) which sum to give the coefficient of the x- term (- 3)
The factors are - 1 and - 2 , since
- 1 × - 2 = + 2 and - 1 - 2 = - 3 , then
(x - 1)(x - 2) = 0 ← in factored form
Equate each factor to zero and solve for x
x - 1 = 0 ⇒ x = 1
x - 2 = 0 ⇒ x = 2